Is there a role for locoregional treatment of the primary tumor in de novo metastatic breast cancer in the era of tailored therapies?: Evidences, unresolved questions and a practical algorithm. (January 2021) - Pons-Tostivint, E.; Alouani, E.; Kirova, Y.; Dalenc, F.; Vaysse, C.
Graphical abstract: Biological effects of loco-regional treatment in dnMBC. Highlights: LRT of the primary tumor in dnMBC remains steadily proposed by clinicians over decades. LRT in dnMBC is a shared decision between medical, radiation and surgical oncologists. LRT should be considered after controlled disease by systemic therapies and must depend on IHC subtypes. Reassuring data are now available regarding exclusive loco-regional radiation therapy as a means of LRT. Abstract: Improvements in systemic therapies have changed the face of de novo metastatic breast cancer (dnMBC), with a 5-year survival rate exceeding 25 %. Increasing evidence suggests that a subset of patients could benefit from a locoregional treatment (LRT) with prolonged survival, although the diversity of publications on the subject make it difficult to draw any conclusions. In this review, we summarize the available data on retrospective, prospective and current ongoing clinical trials. Since factors such as tumor biology, pattern of metastatic dissemination and the timing of the treatment are closely linked to the therapeutic strategy, we focus on papers which include these aspects. We discuss recent studies indicating that exclusive radiotherapy provides results comparable with those obtained by surgery. We will then discuss the biological rationale for LRT. Finally, we propose a decision-tree to select the optimal candidates for LRT in dnMBC patients.